2010
DOI: 10.5194/angeo-28-941-2010
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric precursors for crustal earthquakes in Italy

Abstract: Abstract.Crustal earthquakes with magnitude 6.0>M≥5.5 observed in Italy for the period 1979-2009 including the last one at L'Aquila on 6 April 2009 were considered to check if the earlier obtained relationships for ionospheric precursors for strong Japanese earthquakes are valid for the Italian moderate earthquakes. The ionospheric precursors are based on the observed variations of the sporadic E-layer parameters (h Es, fbEs) and foF2 at the ionospheric station Rome. Empirical dependencies for the seismo-ionos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
43
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 27 publications
(38 reference statements)
3
43
0
2
Order By: Relevance
“…The approach proposed by Khegai (2006, 2008) and successively developed by Perrone et al (2010) may be considered an improved attempt to obtain a quantitative relationship for seismo-ionospheric anomalies. The main idea is based on the results of a theoretical analysis by Kim et al (1993Kim et al ( , 1994, who showed that the electric field above the preparation zone of future earthquakes can penetrate into the ionosphere to form a dense sporadic layer Es at 120-140 km height above the earthquake preparation zone.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The approach proposed by Khegai (2006, 2008) and successively developed by Perrone et al (2010) may be considered an improved attempt to obtain a quantitative relationship for seismo-ionospheric anomalies. The main idea is based on the results of a theoretical analysis by Kim et al (1993Kim et al ( , 1994, who showed that the electric field above the preparation zone of future earthquakes can penetrate into the ionosphere to form a dense sporadic layer Es at 120-140 km height above the earthquake preparation zone.…”
Section: Introductionmentioning
confidence: 99%
“…A distinguishing feature of our analysis is the multiparameter approach, which takes into account the variations of three parameters simultaneously in Es and regular F2 layers (Korsunova and Khegay, 2008;Perrone et al, 2010;Villalobos et al, 2016). Perrone et al (2010) have considered all crustal M > 5.0 earthquakes and a hypocentral depth < 50 km, and with the ionospheric observatory inside the preparation zone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 736 M>6.0 earthquakes worldwide during 2002-2010 were statically studied using TEC data, and the feature of LT variation in ionospheric anomalies was confirmed . Moreover, empirical dependencies of the seismo-ionospheric disturbances relating the earthquake magnitude and the epicenter distance were discussed by means of statistical analysis (Perrone et al, 2010;Saradjian and Akhoondzadeh, 2011). However, the existence of the seismo-ionospheric precursors is still an open issue because of high ionospheric variability and the influence of solar activity.…”
Section: Introductionmentioning
confidence: 99%
“…В этом контексте рядом исследователей выска-зывается мнение, что предвестники в ионосфе-ре можно идентифицировать лишь с некото-рой вероятностью из-за большой изменчиво-сти этой области околоземного пространства, так как имеется часть ионосферных аномалий, которые не сопровождаются сейсмическими событиями даже в спокойных геомагнитных условиях [Perrone et al, 2010].…”
unclassified